Laser-induced topology optimized amorphous nanostructure and corrosion electrochemistry of supersonically deposited Ni30Cr25Al15Co15Mo5Ti5Y5 HEA coating based on AIMD. (20th April 2022) - Yan, Xue; Zhang, Cheng; Li, Yangshuai; Yi, Youjian; Cui, Ziruo; Han, Bingyuan
Highlights: New NGs HEA coating topology optimized by laser after SPD is proposed. Quasi isotropic and amorphous structure are formed with random orientation. DSC baseline starts to shift when Tg reached to 939.37 ℃ as step appearing. Dispersion peak and lattice fringe in XRD and TEM shows incomplete nucleation. Oxidation passivation layer of LTO coating insulated the corrosion medium. Abstract: A novel Ni30 Cr25 Al15 Co15 Mo5 Ti5 Y5 high-entropy alloy (HEA) coating was irradiated to optimize its internal structure via laser after supersonic particle deposition (SPD). Owing to the high energy density of the laser and large temperature gradient, the crystallization process of the molecules and atoms in the coating was restrained and supercooling occurred. Experimental results showed that a considerable number of nano-crystal grains precipitated and amorphous structures were formed because of the random orientation of the crystals. The baseline of differential scanning calorimetry scans obtained for the coating started to shift at the T g of 939.37 ℃ and a step was observed. Multiple dispersion peaks and lattice fringes indicated that the nucleation of the irradiated laser-induced topology optimized (LTO) coating was incomplete. The laser-induced topology optimizing treatment led to quasi-isotropy in the SPD coating. Furthermore, the LTO coating exhibited a residual stress of 18.4 MPa, stress-strain response, and fatigue limit of 265 MPa. Hence, the LTO coating exhibited higher performance than the unirradiated SPD coating. The Nyquist and Bode electrochemical impedance spectra of the LTO coating, including two relaxation processes, indicated that the corrosion process steadily recovered to the equilibrium state. This implies that the uniform oxidation passivation layer on the surface of the LTO coating insulated the material from the corrosive medium, protecting the substrate from further corrosion, thus enhancing the structural security of the material for use in super-intense laser facility applications. Graphical Abstract: Graphical Abstract Image, graphical abstract .